Additional description on morphology of the Misol snake eel from Taiwan, with four verified barcodes of life sequences - Chiu, Yung-Chieh; Chen, Hong-Ming; Shao, Kwang-Tsao (Zootaxa, 2022)
An additional description of the Misol snake eel Yirrkala misolensis (Günther, 1872) is reported on the basis of 9 specimens collected from Dong-gang and Ke-tzu-liao, southwestern Taiwan. The species was previously reported from Indonesia and Australia and then extends northward to Taiwan and Japan, and was lacking adequate characterization on morphology. A detail description, fine condition of fresh photographs and 4 partial CO1 sequences are provided for the first time.